Anthracyclines during induction therapy in acute myeloid leukaemia: a systematic review and meta‐analysis. (8th February 2013) - Teuffel, Oliver; Leibundgut, Kurt; Lehrnbecher, Thomas; Alonzo, Todd A.; Beyene, Joseph; Sung, Lillian
Summary This systematic review and meta‐analysis compared the efficacy of different anthracyclines and anthracycline dosing schedules for induction therapy in acute myeloid leukaemia in children and adults younger than 60 years of age. Twenty‐nine randomized controlled trials were eligible for inclusion in the review. Idarubicin (IDA), in comparison to daunorubicin (DNR), reduced remission failure rates (risk ratio (RR) 0·81; 95% confidence interval (CI), 0·66–0·99; P = 0·04), but did not alter rates of early death or overall mortality. Superiority of IDA for remission induction was limited to studies with a DNR/IDA dose ratio <5 (ratio <5: RR 0·65; 95% CI, 0·51–0·81; P < 0·001; ratio ≥5: RR 1·03; 95% CI, 0·91–1·16; P = 0·63). Higher‐dose DNR, compared to lower‐dose DNR, was associated with reduced rates for remission failure (RR 0·75; 95% CI, 0·60–0·94; P = 0·003) and overall mortality (RR 0·83; 95% CI, 0·75–0·93; P < 0·001), but not for early death. Comparisons of several other anthracycline derivates did not reveal significant differences in outcomes. Survival estimates in adults suggest that both high‐dose DNR (90 mg/m2 daily × 3 or 50 mg/m2 daily × 5) and IDA (12 mg/m2 daily × 3) can achieve 5‐year survival rates of between 40 and 50 percent.